2017
DOI: 10.4018/978-1-5225-0495-5.ch005
|View full text |Cite
|
Sign up to set email alerts
|

A Social Knowledge Management Platform for Universal Primary Education Online

Abstract: Social knowledge management is a framework that allows its users to create and modify content collaboratively using social media and web 2.0 technologies. Social knowledge management can also be defined as the management of social knowledge where it is aimed towards social development. India today is facing a huge rural-urban divide with regard to poor learning achievement at the elementary level in remote rural areas. Remote rural schools are engulfed with problems such as the unavailability of good quality t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Ghalomi et al (2013) viewed it as a decision that involves the use of knowledge for organizational efficiency. Bandyopadhyay et al (2017) empirically observed that by the application of knowledge, lecturers developed interesting and valuable teaching and learning activities.…”
Section: Knowledge Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghalomi et al (2013) viewed it as a decision that involves the use of knowledge for organizational efficiency. Bandyopadhyay et al (2017) empirically observed that by the application of knowledge, lecturers developed interesting and valuable teaching and learning activities.…”
Section: Knowledge Applicationmentioning
confidence: 99%
“…In the individual level, modern lecturers are not only responsible for lesson delivery, but also for accumulating and enriching the knowledge. KM facilitates the academics to create new knowledge and process the collected one based on their requirements and students' capabilities (Bandyopadhyay et al, 2017). Supermane and Tahir (2018) stated the education system as an efficient medium of a country that can enrich its competitiveness.…”
Section: Introductionmentioning
confidence: 99%